(untitled) (Journal of Hama University, 2020)
Non- governmental organizations are an important synonym for providing diverse health services during the current Syrian crisis. The satisfaction of the beneficiaries of these services is an important indicator in assessing the role of these organizations in providing their services. Therefore, the present study aimed to evaluate the satisfaction of 600 randomly selected beneficiaries (200 from each organization) about the role of 3 organizations in providing health services during the Syrian crisis in Lattakia city. Using a questionnaire developed by the researcher for this purpose, the results showed a high degree of satisfaction with the availability of all necessary medical equipment, the quality of ventilation and lighting conditions, and the material possibilities available to these organizations. This is in addition to the diversity of the services provided and their compatibility with the needs of the beneficiaries, the flexibility of the staff and the accuracy of providing the service in a timely manner. The beneficiaries did not acknowledge that it was difficult to communicate with the administration. The study recommended turning to the media to highlight the services provided by these associations, encouraging material and human support for the associations. Conducting a patient satisfaction assessment regularly every 6 months, developing a complaints and suggestions box within the associations, and conduct more researches on the subject with larger samples and more representative method.